PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIRTUAL REALITY UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR - Mardiki Supriadi; L. Virginayoga Hignasari (STMIK Budi Darma, 2019)
Educators use various methods to explain the material so that learning objectives can be achieved, one of the methods is by utilizing learning media. The purpose of using learning media in learning activities is to facilitate communication and learning. The use of media in learning activities aims to attract the attention of students and strengthen their concentration when receiving material from educators.The development of virtual reality media is an effort to realize educational goals. One of the success of learning lies in the ability of students' learning outcomes. Learning outcomes are very important for students as a benchmark of the extent to which students understand the material delivered by educators. Virtual reality media make learning outcomes the basis of development. The purpose of this study is to produce products in the form of virtual reality media to improve learning outcomes of elementary school students.This research is a development research with 4D development model from Thiagarajan. This development model consists of the stages define (design), design (design), develop (development), and disseminate (deployment). The research and development stage is carried out until the disseminate stage with the publication of articles and a trial process to students which is done on a limited basis. Data collection instruments in the form of a questionnaire distributed to experts in the material, media, and field application.Student learning outcomes of the experimental class and the control class can be concluded that the virtual reality-based learning media used in the experimental class are stated to be more effective and can improve student learning outcomes by a percentage of 100% while the control class gets 77.3%.Keywords: learning media, virtual reality, learning outcomes